The Branding Serambi Madinah: Half-hearted Politics of Identity in Gorontalo City - Zeffry Alkatiri (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
Indonesia started a reformation process and transition to democracy marked by the issuance of Local Autonomy Law year 1999/2014 and 2015. These regulations have pushed the will of every local area to rethink of their local identity and cultural values within the context of local wisdom in various areas in Indonesia. Based on the above problem, this article shows that the issue of the implementation of Local Autonomy Law no. 9 year 2015 has been interpreted into different thoughts related to local cultural context in Gorontalo. One of them is to construct branding for the capital province which is Serambi Madinah by imitating Serambi Mekah created by Aceh Province. The objective of this article is to study the factors that contribute to the failure of Gorontalo’s branding as Serambi Madinah, based on the terms and conditions of city branding standard as the parameter. The data of this qualitative research were collected from various literature studies and one-month field observations (August - September2018) in Gorontalo. The analysis was conducted using the theory of politics of identity and concepts related to city branding. This article questions the reasons and background of Serambi Madinah city branding: what is the reason and background of the Serambi Madinah branding? Is this branding in accordance with the terms and conditions of a city branding standard? The article concludes that the creation of the Serambi Madinah branding is a practice of identity politics of the elites to show their identity after separating from the province of North Sulawesi.